The Characteristics of Users in the Adoption of Low Loss Microwaves Transmission Glass: A Conceptual Paper - Musa, Haslinda; Safri, Nursyairalia; Yunus, Ahmad Rozelan; OTHMAN , MOHD AZLISHAH (Elsevier Ltd, 2016)
This paper aims to examine the relationship between users' characteristics towards adoption the LLMTG. These relations were found correleted in its intention to adopt this type of glass in building structures. Despite the indication provided by numerous empirical studies, the organization that adopt the LLMTG will gain more competitive advantages and improvement. It is strongly believed that this attempt would contribute both to knowledge of the diffusion of inovation and to implications for practice by assisting the industry to understand the important factors when adopting innovation. Rich data will be collected using questionnaire among managers from all industrial in Malaysia.